False Recognition in Short-Term Memory – Age-Differences in Confidence - Sikora-Wachowicz, Barbara; Lewandowska, Koryna; Keresztes, Attila; Werkle-Bergner, Markus; Marek, Tadeusz; Fafrowicz, Magdalena (Frontiers in Psychology, 2019)
Compared to young adults, older adults are more susceptible to endorse false memories as genuine and exhibit higher confidence in their decisions to do so. While most studies to date have addressed this phenomenon in the context of episodic memory, the literature on age-differences in false recognition during short-term memory (STM) is scarce. Hence, the present study investigated age-related differences in the rate of false alarms (FA) and subsequent confidence judgements in STM. Thirty-three young and thirty-three older adults performed a visual short-term recognition memory task. In each trial, participants encoded a single abstract object, then made a “same” or “different” decision on a subsequent test, followed by a confidence judgement. We found significant age-related differences in performance as measured by the sensitivity index (d’), but not in the rate of FAs. Older adults were more confident in their erroneous recognition decisions than younger adults. The results are discussed in the context of age-differences in monitoring and associative processes.